(untitled) (Research, Society and Development, 2022)
The objective of this review was to verify the available scientific evidence on allocation and concealment methods, and the statistical analyses used in randomized clinical trials (RCTs) on bilateral CTS. An integrative literature review was conducted, based on searches of databases for the period from 2014 to 2021. One-hundred-and-ten articles were found, of which 22 were considered eligible for inclusion. The statistical analyses methods used in the presence of bilateral pathologies was not clear in six (27.27%) cases and was inappropriate in another six (27.27%). A further five (22.72%) articles included only the most severely affected wrist for evaluation, while data from the right and left wrist were analyzed and described separately in four (18.18%) reports. Finally, only one (4.54%) RCT showed an adequate statistical approach. RCTs on clinical and surgical therapy of CTS do not use statistical models that include data repetition due to bilaterality when assessing outcomes.